188k views
0 votes
Find (f + g)(x) and (f g)(x) for f(x) = 6x2 + 5 and g(x) = 7 – 5x.

User Ruwan
by
6.5k points

1 Answer

4 votes

Answer:

see explanation

Explanation:

(f + g)(x) = f(x) + g(x)

f(x) + g(x)

= 6x² + 5 + 7 - 5x ← collect like terms

= 6x² - 5x + 12

(fg)(x) = f(x) × g(x)

= (6x² + 5)(7 - 5x)

Each term in the second factor is multiplied by each term in the first factor

=6x²(7 - 5x) + 5(7 - 5x) ← distribute both parenthesis

= 42x² - 30x³ + 35 - 25x

= - 30x³ + 42x² - 25x + 35

User Kamran Kausar
by
6.1k points